Avaliação da razão Lidar do satélite CALIPSO utilizando a profundidade óptica de aerossóis obtidos por um fotômetro solar da rede AERONET em Petrolina/PE, Brasil - Oliveira, Nara Poliana Meneses de (2018)
There are many factors that turn the quantification of the aerosol influence on climate change processes challenging. These factors are associated to the uncertainties in the distribution and properties of aerosols and clouds, as well as their global interactions. With the purpose of reducing those uncertainties, the National Aeronautics and Space Administration (NASA) in collaboration with the Centre National d'Études Spatiales (CNES), launched the Cloud-Aerosol LIDAR and Infrared Pathfinder Satellite Observation (CALIPSO) satellite, which has on board a Cloud-Aerosol LIDAR with Orthogonal Polarization (CALIOP), consisting of a light detector and tracker Light Detection and Ranging (LIDAR). This system performs a vertical sounding of thin clouds and aerosols properties around the globe as the satellite passes. A number of algorithms recovers the optical properties of the atmosphere along the pathway where the CALIOP laser propagates, and to ensure the quality of the results, it is necessary to validate the data by different instruments and/or methods. For this reason, ground-based measurements are necessary for calibration purposes. In this study a methodology was used to validate the Lidar Ratio from CALIOP, by obtaining the aerosol optical depth data from 2007-2016 of a sun photometer part of the AERONET network and installed in Petrolina-PE in the Brazilian Northeast. The CALIOP data were obtained using 54 coincident measurements under cloudfree conditions, which corresponds to 31% of all existing measurements in the proximity of Petrolina/PE from 2007-2016. The Lidar Rations from CALIOP HERA algorithm and AERONET/CALIPSO technique (A/C-Technique), developed by Lopes et al. (2013), presented a percentage difference of 14.76 ± 4.79% from Lidar Ratio values of the A / C technique compared to the CALIPSO model. A study case carried out on 01/11/2007, in which the CALIPSO satellite recorded a mean distance of 48 km in relation to the photometer, the optical aerosol depth resulted in 0.038 / 0.031, and the Lidar Ratio 40 sr / 45 sr (dust), respectively, with a percentage difference of 11%. Comparing the values of the A / C Model with the CALIOP for the 10-year study, the overall model indicated an underestimation of the Lidar Ratio values, assuming that it may not be suitable for the study region. A super estimation may be associated to the CALIOP calibration, especially due to the influence of the South Atlantic Anomaly of the Earth’s magnetic field that may affect the accuracy of the system’s measurements.